Applications of Rozen’s Reagent in Oxygen-Transfer and C–H Activation Reactions - Singh, Kuldeep; Kulbir, Kulbir; Gupta, Tarang; Kaur, Rajneesh; Singh, Raman (Synthesis, 2019)
Rozen’s reagent (hypofluorous acid–acetonitrile complex, HOF·MeCN) is a robust nonspecific oxygen-transfer reagent and became a proven tool for the oxidation of difficult-to-oxidize molecules. It has been applied to instant oxygen transfers to functional groups such as alkenes, alkynes, and aromatic hydrocarbons, epoxidation, oxidation of alcohols, amines, and alkynes, oxygen-transfer reactions with nitrogen, phosphorus, and sulfur-containing substrates, and α-hydroxylation of carbonyl groups. Apart from being a potential green oxidizing agent, the complex has applications in 18O-labeling and C–H functionalization strategies. Recent uses of Rozen’s reagent in developing nanomaterials and oxidized expanded graphite indicate the enormous potential of the reagent. These aspects are discussed in this review.1 Introduction2 Synthesis and Physical Properties3 Safety and Handling4 Oxygen-Transfer Reactions4.1 General Mechanism of Oxygen Transfer4.2 Epoxidation4.3 Oxidation of Alkynes4.4 Oxidation of Aromatic Alcohols and Phenols4.5 Oxidation of Nitrogen-Containing Compounds4.6 Conversion of Aldehydes into Nitriles4.7 Oxidation of Alcohols and Ethers4.8 Oxidation of Sulfur-Containing Compounds4.9 Oxygen-Transfer Reaction with Phosphine, Phosphite, and Phosphinite Compounds5 C–H Activation Reactions5.1 Hydroxylation of Nonactivated Tertiary Saturated Carbon Center5.2 Hydroxylation of Aromatic Carbon Center5.3 α-Hydroxylation of Carbonyl Group5.4 Activation of α-Hydrogens of α-Amino Acids6 Other Uses7 Green Chemistry and Rozen’s Reagent8 Experimental Problems9 Further Applications10 Conclusions
Keywords: Rozen’s reagent; Rozen oxidation; C–H functionalization; oxygen-transfer reaction; 18O labeling; hypofluorous acid–acetonitrile complex; green synthesis